HRM and the use of personnel services: an empirical analysis of German firms - Alewell, Dorothea; Hauff, Sven; Weiland, Katrin; Thommes, Kirsten (International journal of manpower, 2011)
Purpose - The purpose of this paper is to analyse how characteristics of the HR department and HR work, which relate to resource availability and resource needs, influence HR outsourcing. The study examines the subject of human resource (HR) outsourcing.Design methodology approach - The potential influence of firms' characteristics on HR outsourcing is analysed theoretically and empirically. The dataset (n=1,021) covers a broad spectrum of personnel services and is based on computer-aided telephone interviews with chief executives and human resource managers of German firms.Findings - Generally, we find that firm size and previous reorganization activities significantly raise the probability of an HR outsourcing. In contrast, there is no overall significant influence of central characteristics of HR work or the HR department on HR outsourcing in general.Originality value - Although there is a trend toward the outsourcing of work, little research is being done on the relationship between the expected effects of outsourcing, the make-or-buy decision of decision makers, and the firm's characteristics themselves. This study sheds some more light on the relationship between HR outsourcing and firms' characteristics and finds some interesting relationships.